2015
DOI: 10.1371/journal.pone.0131219
|View full text |Cite
|
Sign up to set email alerts
|

The Low-Cost Compound Lignosulfonic Acid (LA) Exhibits Broad-Spectrum Anti-HIV and Anti-HSV Activity and Has Potential for Microbicidal Applications

Abstract: ObjectivesLignosulfonic acid (LA), a low-cost lignin-derived polyanionic macromolecule, was extensively studied for its anti-HIV and anti-HSV activity in various cellular assays, its mechanism of viral inhibition and safety profile as potential microbicide.ResultsLA demonstrated potent inhibitory activity of HIV replication against a wide range of R5 and X4 HIV strains and prevented the uptake of HIV by bystander CD4+ T cells from persistently infected T cells in vitro (IC50: 0.07 – 0.34 μM).LA also inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 72 publications
1
37
0
2
Order By: Relevance
“…Ag NPs and fullerene derivatives have been used for antiviral studies. In sharp contrast, no studies on nano‐ or microscaled antiviral lignin materials have been published, although antiviral properties have been reported for different types of lignins . Ag NPs are well known for their antibacterial effects .…”
Section: Effects Of Nano‐ and Microsized Lignins On Living Organismsmentioning
confidence: 99%
“…Ag NPs and fullerene derivatives have been used for antiviral studies. In sharp contrast, no studies on nano‐ or microscaled antiviral lignin materials have been published, although antiviral properties have been reported for different types of lignins . Ag NPs are well known for their antibacterial effects .…”
Section: Effects Of Nano‐ and Microsized Lignins On Living Organismsmentioning
confidence: 99%
“…For textiles, there are special requirements such as non-toxicity to the consumer, namely cytotoxicity, allergy or irritation and sensitization. In other recent studies, lignosulfonic acid is reported to exhibit broad-spectrum anti-HIV (human immunodeficiency virus) and anti-HSV (herpes simplex virus) properties [22,23]. Thus, Qiu investigated the anti-HIV-1 activity-potential of lignosulfonates as a microbicide to prevent HIV-1 sexual transmission [23].…”
mentioning
confidence: 99%
“…investigated lignosulfonic acid regarding HIV antiviral activity revealing lignosulfonic acid to be a potent inhibitor of the HIV replication. They also prevent an uptake of the virus by CD4T cells from persistently infected T cells in vitro [56]. The antiviral activity of lignin products is also shown for CMV and HSV-1 and HSV-2.…”
Section: Lignin Antimicrobial Activitymentioning
confidence: 87%